The 2nd Asian Space Conference Hanoi, Vietnam, 8-11 November 2005, Conference Material - Geo-Informatics and Space Technology Development Agency (GISTDA); The International Institute for Geo-Information Science and Earth Observation (ITC); The International Institute of Air and Space Law (IIASL); The Netherlands, The International Institute for Asian Studies (IIAS); Vietnam, The Vietnam Association of Geodesy, Cartography and Remote Sensing (VGCR) (Hanoi, Vietnam AVG, 2005)
Satellites, Applications, Socio-Economics and Regulatory Regimes
Title from title screen
Keywords: Asian Conference -- Space; Astronautics -- Conference